PERAN GURU PAI DALAM MENANAMKAN SIKAP SOSIAL SISWA KELAS VII DI MTS AISYIYAH 1 PALEMBANG - Muhammad Yusuf; Abdullah Idi; Abu Mansur; Herman Zaini (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
This research is motivated by social problems that occur today in daily relationships, there are still many children's behaviors that go out of the rules. Therefore, social attitudes need to be instilled so that children can avoid social problems. In instilling social attitudes, teachers as educators have a significant influence on the development of student behavior, especially teachers of Morals. The purpose of this study was to reveal how the role of Aqidah Akhlak teachers in instilling social attitudes and to reveal the supporting and inhibiting factors in instilling social attitudes in grade VII students of MTs Aisyiyah 1 Palembang.This study is descriptive qualitative research. The type of data in this study is qualitative data obtained from the results of observations, interviews, and documentation. Sources of data in this study include primary and secondary data. Data analysis by reducing data, presenting data, and then verifying the data.The results of this study are that Aqidah Akhlak teachers have a role in instilling students' social attitudes both inside and outside the classroom. The first role of Aqidah Akhlak teachers is in the classroom including as an educator, in the formator, motivator, and facilitator. Outside the classroom, the teacher acts as a second parent and role model. The supporting factors for aqidah akhlak teacher in instilling student social attitudes are a supportive school environment, such as setting aside pocket money to donate to orphanages, strong self-awareness for change, and a supportive home environment. While the inhibiting factor is a technology that is misused by students and tends to cool off on its own without paying attention to social conditions or the surrounding environment, unsupportive home environments, and limited time for teachers to educate and supervise students when they are outside the school environment.